Disiplin Kerja Pegawai Negeri Sipil Di Kantor Dinas Komunikasi Dan Informatika Provinsi Maluku - Lestari, Ayu; Ohoiwutun, Stanislaus.K.; Rahanra, Ivonny Y. (SENGKUNI Journal (Social Science and Humanities Studies), 2023)
Civil Servant Work Discipline is defined as a form of employee attitude in respecting, appreciating, complying with and obeying existing regulations, both written and unwritten and being able to carry them out and not avoiding accepting sanctions if they violate their duties and authorities that was given to him. Enforcing discipline is important for an agency, because discipline contains rules that must be obeyed by employees. To achieve good results in accordance with the goals that have been set, it is necessary to have good work discipline from employees. This study aims to find out how Preventive Discipline and Corrective Discipline and Efforts to improve the work discipline of Civil Servants at the Office of Communication and Information Technology of Maluku Province with a total of five informants. The type of research used is qualitative research with a phenomonology approach by obtaining data from interviews, observations, and direct documentation in the field. The results of this study indicate that it can be said to be quite good because in the preventive and corrective disciplinary processes the types of sanctions that have been issued are verbal warnings only because the types of violations that occur are categorized as minor violations while efforts to increase discipline are strengthening good behavior starting from the leadership of the Communications Service and Informatics of Maluku Province.